Violência perpetrada por parceiro íntimo sob efeito de substâncias psicoativas narrada pela mídia impressa paraense - PAIXÃO, Victor Assis Pereira da (2019)
INTRODUCTION: Violence against women is a global phenomenon, prevalent in societies that have patriarchal values in their culture, where gender inequality predominates. In this context, the consumption of psychoactive substances is one of the main factors associated with violence, demonstrating the need for research from the perspective of the aggressor. OBJECTIVE: To analyze the violence against women perpetrated by intimate partners on the effect of alcohol or psychoactive drugs, narrated by the print media in the year 2017. METHODOLOGY: This is a documentary study, restrosptive, with a quantitative approach. The information was collected from notes published in the O Liberal / Belém-Pa periodicals from January to December 2017, available at the Arthur Vianna Library, analyzed from the construction of charts and tables. RESULTS AND DISCUSSIONS: from the analysis, 30 cases of marital violence, with a predominance of 83.33% of physical violence, were recorded in the newspapers of 2017, alcohol was associated with violence perpetrated against a partner in 23.33% of the cases , revealing the need to seek studies related to alcohol consumption and violence, considering their impacts in the family context. FINAL CONSIDERATIONS: Although law 11.340 of 2006, characterized as the Maria da Penha Law, arises with the precept of punishing the aggressor to ensure the safety of the victim, in article 35, item V, provide for rehabilitation spaces for the aggressor, in consonant with the federal constitution of 1988, which guarantees access to health as a right of all and a duty of the state, in addition to the organic health law 8,080 of 1990, care must be taken to ensure the health of the aggressor, not penalties related to the ingestion of beverages alcoholic and psychoactive substances, but in the context of violence, understanding it with a health problem.